2009
DOI: 10.1259/dmfr/59263880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the severity of temporomandibular joint osteoarthritic changes related to age using cone beam computed tomography

Abstract: Degenerative arthritis is an age-related disease. The progression and severity of osseous changes in the condylar head and mandibular fossa are increased with age. In older age groups, patients are expected to have more frequent and severe progressive degenerative bony changes due to the development of TMJ osteoarthritis than patients in younger age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
180
8
13

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(220 citation statements)
references
References 37 publications
19
180
8
13
Order By: Relevance
“…15,16 In our study, 78% of the patients were female and 22% were male. LeResche 15 found that pain in the temporomandibular region is twice as common in women than in men.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…15,16 In our study, 78% of the patients were female and 22% were male. LeResche 15 found that pain in the temporomandibular region is twice as common in women than in men.…”
Section: Discussionmentioning
confidence: 54%
“…27,28 In our study, flattening and osteophyte degenerative bone changes were the predominant findings. This was verified by Güler et al 24 using MRI in patients who had bruxism, by Alexious et al 16 who, using CBCT, found erosion, flattening and osteophytes to be the most common radiographic finding of the condyle and by Campos et al, 23 who found osteophytes and erosion to be more prevalent in their MRI study.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations